Justice perspectives of women with disability: An Australian story. Issue 2 (May 2021) - McCulloch, Jude; Maher, JaneMaree; Walklate, Sandra; McGowan, Jasmine; Fitz-Gibbon, Kate
The article explores the meaning of 'justice' for women with disability who have experienced and reported violent crimes, typically, sexual assault and family violence. It contributes to the small body of literature that considers justice as articulated by those who have experienced violence and represents the only published research that brings to the fore perspectives on justice from the viewpoint of women with disability. Based on interviews and focus groups with 36 women with disability in the Australian states of Victoria and New South Wales, it explores these women's 'justice' ideals and the gap between those ideals and the responses they received from the service and criminal justice systems. Mostly, the women's desired outcomes in response to reports of violence were focused on recognition of what had occurred, an acknowledgement of their rights and status, and a pathway to security and safety. These desires related to justice were linked to being able to leave a situation of danger, retain custody of children, have access to care and advocacy services and gain a sense of safety or, sometimes, simply survive. The women's desires underline how inadequate the typical narrow criminal justice response is in meeting the 'justice' ideals and needs of women with disability because it is focused on establishing the guilt or otherwise of the defendant and on any subsequent punitive sanctions. These women's experiences and insights highlight the impact of discrimination and inequality on both justice as an ideal and justice as it is experienced.